Biomaterial strategies for engineering implants for enhanced osseointegration and bone repair - Agarwal, Rachit (Adv Drug Deliv Rev, 2015)
Bone tissue has a remarkable ability to regenerate and heal itself. However, large bone defects and complex fractures still present a significant challenge to the medical community. Current treatments center on metal implants for structural and mechanical support and auto- or allo-grafts to substitute long bone defects. Metal implants are associated with several complications such as implant loosening and infections. Bone grafts suffer from donor site morbidity, reduced bioactivity, and risk of pathogen transmission. Surgical implants can be modified to provide vital biological cues, growth factors and cells in order to improve osseointegration and repair of bone defects. Here we review strategies and technologies to engineer metal surfaces to promote osseointegration with the host tissue. We also discuss strategies for modifying implants for cell adhesion and bone growth via integrin signaling and growth factor and cytokine delivery for bone defect repair.